Analisis Konsep Tritunggal Allah dan Implikasinya berdasarkan Injil Yohanes: An Analysis of the Concept of the Trinity and Its Implications based on the Gospel of John - Djonny Pabisa; Pratiwi Eunike; Tan Winda (Journal of Religious and Socio-Cultural, 2024)
The concept of the Trinity, referring to God as one essence in three Persons: the Father, the Son, and the Holy Spirit, has been a subject of debate throughout Christian history. Although this doctrine is widely accepted in Christianity, its interpretation and understanding often vary among different Christian denominations and traditions. The type of research used is qualitative with a text analysis approach including text selection, text analysis, interpretation and theological context, and a study of relevant literature. The result is the concept of the Trinity in the Gospel of John, affirming the existence of one God who exists in three Persons: the Father, the Son, and the Holy Spirit. The three persons are distinct but equal and the same in essence and divinity. They interact and relate to each other in ways that cannot be understood by humans because they are carried out according to God's incomprehensible ways. The implication of understanding the principle of the Trinity opens a new perspective on how we can interact and work together in various aspects of our lives. Although we are different, we are interconnected and need each other. Like the Trinity, we can work together in harmony, supporting each other, and achieving greater goals together. Konsep Tritunggal Allah, merujuk kepada Allah sebagai satu esensi dalam tiga Pribadi: Bapa, Anak, dan Roh Kudus, telah menjadi subjek perdebatan sepanjang sejarah Kristen. Meskipun doktrin ini secara umum diterima secara luas dalam kekristenan, namun interpretasi dan pemahamannya seringkali bervariasi di antara berbagai denominasi dan tradisi Kristen. Jenis penelitian yang digunakan adalah kualitatif dengan pendekatan analisis teks meliputi seleksi teks, analisis teks, penafsiran dan konteks tologis, dan kajian literatur yang relevan. Hasilnya, konsep Tritunggal Allah dalam Injil Yohanes, menegaskan adanya satu Allah yang eksis dalam tiga Pribadi: Bapa, Anak, dan Roh Kudus. Ketiga pribadi berbeda namun setara dan sama dalam esensi dan keilahian. Ketiga pribadi saling berinteraksi dan saling berelasi satu sama lain dalam cara yang tidak dapat dipahami oleh manusia karena dilakukaan menurut cara-Nya Allah yang tidak dapat dijelaskan dengan akal manusia. Implikasi pemahaman tentang prinsip Tritunggal Allah membuka perspektif baru tentang bagaimana kita dapat berinteraksi dan bekerja bersama dalam berbagai aspek kehidupan kita. Meski kita berbeda, kita saling terkait dan membutuhkan satu sama lain. Seperti Tritunggal Allah, kita bisa bekerja bersama dalam harmoni, saling mendukung, dan mencapai tujuan yang lebih besar bersama-sama.